Effects of attribute framing on cognitive processing and evaluation - Kuvaas, Bård; Selart, Marcus (Organizational Behavior and Human Decision Processes, 2004)
Whereas there is extensive documentation that attribute framing influences the content of peoples thought, we generally know less about how it affects the processes assumed to precede those thoughts. While existing explanations for attribute framing effects rely completely on valence-based associative processing, the results obtained in the present study are also consistent with the notion that negative framing stimulates more effortful and thorough information processing than positive framing. Specifically, results from a simulated business decision-making experiment showed that decision makers receiving negatively framed information had significantly better recall than those receiving positively framed information. Furthermore, decision makers in the negative framing condition were less confident than decision makers in the positively framed condition. Finally, compared to a no-framing condition, decision makers receiving positive framing deviated significantly more in evaluation than decision makers receiving negative framing did.